SWOT analysis of Ecotourism development in Sembilang National Park, Banyuasin Regency, South Sumatra, Indonesia - Alimin Alimin; Rozirwan Rozirwan; Elisa Wildayana; Riswani Riswani (Dinasti International Journal of Education Management And Social Science, 2024)
Tourism is one of the dynamic industrial activities for a country's income. Tourism can take the form of ecotourism with potential factors for nature conservation and development. Ecotourism is a form of tourism that is primarily inspired by the natural history of an area, including the area's indigenous culture. Effective sustainable ecotourism management must use strategic planning. Strategic planning can use the SWOT matrix. In general, the strengths of Sembilang National Park are the uniqueness of migratory birds from Siberia that do not exist anywhere else and the presence of exotic animal habitats. The weakness of Sembilang National Park is that transportation is still dominated by waterways and there is a lack of clean water sources. The opportunities for Sembilang TN include financial assistance and international recognition. Meanwhile, the threat to Sembilang National Park is weather conditions which greatly affect waterways. From the weighting results, it is found that the position of Sembilang TN is on the X axis with a value of 9. So it can be concluded that Sembilang TN is at a positive point on the The position of the Sembilang National Park development strategy is in Quadrant I, namely the strategy of utilizing all strengths to seize and exploit maximum opportunities.